2006
DOI: 10.4278/0890-1171-21.1.16
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With Smoking Cessation Counseling at Clinical Encounters: The Behavioral Risk Factor Surveillance System (BRFSS) 2000

Abstract: Smoking cessation counseling may be provided preferentially on the basis of patient demographics, and often is not provided at all. In a given year, just over half of smoking patients are advised to quit, and such counseling is provided at less than a quarter of clinical encounters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…In comparison, the prevalence of advice to quit by physicians was comparable to our result (51.6% vs 50.7%). Other studies on the topic reported a similar prevalence (17) or a slightly higher prevalence (7) of physician advising. What smokers report and what HCPs report with respect to delivering advice to quit varies widely.…”
Section: Discussionmentioning
confidence: 69%
“…In comparison, the prevalence of advice to quit by physicians was comparable to our result (51.6% vs 50.7%). Other studies on the topic reported a similar prevalence (17) or a slightly higher prevalence (7) of physician advising. What smokers report and what HCPs report with respect to delivering advice to quit varies widely.…”
Section: Discussionmentioning
confidence: 69%
“…The BRFSS data sets have been widely utilized in a milieu of reports and articles. Of recent, these data have been used in studies associated with cardiovascular heart diseases [15], physical activity [16], cancer screenings [17], mental health [18] obesity [19], diabetes mellitus [20], and multiple preventive health behaviors [21, 22]. …”
Section: Methodsmentioning
confidence: 99%
“…Physicians may be more likely to advise quitting to those who are sicker or who have diseases that are considered "smoking-related" (e.g., cardiac, respiratory, or cerebrovascular conditions). [11][12][13][14][15] However, much of this literature is outdated, is focused exclusively on cigarette smoking, and does not examine how advice varies as a function of type of chronic condition and/or tobacco product. Physician behavior surrounding non-cigarette tobacco use is especially understudied.…”
Section: Introductionmentioning
confidence: 99%